Autophagy Receptor Protein Tax1-Binding Protein 1/TRAF6-Binding Protein Is a Cellular Substrate of Enteroviral Proteinase - Mohamud, Yasir; Xue, Yuan Chao; Liu, Huitao; Ng, Chen Seng; Bahreyni, Amirhossein; Luo, Honglin (Frontiers in Microbiology, 2021)
Enteroviruses (EVs) usurp the host autophagy pathway for pro-viral functions; however, the consequence of EV-induced diversion of autophagy on organelle quality control is poorly defined. Using coxsackievirus B3 (CVB3) as a model EV, we explored the interplay between EV infection and selective autophagy receptors, i.e., Tax1-binding protein 1 (TAX1BP1)/ TRAF6-binding protein (T6BP), optineurin (OPTN), and nuclear dot 10 protein 52 (NDP52), known to be involved in regulating the clearance of damaged mitochondria, a process termed mitophagy. Following CVB3 infection, we showed significant perturbations of the mitochondrial network coincident with degradation of the autophagy receptor protein T6BP, similar phenomenon to what we previously observed on NDP52. Notably, protein levels of OPTN are not altered during early infection and slightly reduced upon late infection. Cell culture studies revealed that T6BP degradation occurs independent of the function of host caspases and viral proteinase 3C, but requires the proteolytic activity of viral proteinase 2A. Further investigation identified the cleavage site on T6BP after the amino acid 621 that separates the C-terminal ubiquitin-binding domain from the other functional domains at the N-terminus. Genetic silencing of T6BP and OPTN results in the attenuation of CVB3 replication, suggesting a pro-viral activity for these two proteins. Finally, functional assessment of cleaved fragments from NDP52 and T6BP revealed abnormal binding affinity and impaired capacity to be recruited to depolarized mitochondria. Collectively, these results suggest that CVB3 targets autophagy receptors to impair selective autophagy.